Grandparental Involvement in Children's Learning in Phidim Municipality of Nepal - Bhandari, Laxmi Prasad (Scholars' Journal, 2021)
This study is about grandparental involvement in their children's learning. Its main objective was to find out how the grandparents are involved in their children's learning. It is a qualitative research based on the narrative design. One grandfather, one grandmother, and two grandchildren were purposively selected for in-depth interviews. I used the general inductive approach for coding, categorising and theme generation. The human resource capital approach and the social demand approach were used for analysing the data and drawing conclusion. The grandparents were found involved in motivating their grandchildren, providing proper guidance to them and counselling them in different conditions. They provided emotional and financial support for transforming the grandchildren to human resource capital. They provided different care and practical help to develop behavioural skills on their grandchildren which can contribute for fulfillment of social demand. The grandchildren, their family, the society and the whole country have to recognise the contribution of grandparents properly and pay proper respect to them.